Zooming in. - Stevens, Krista (American City & County, 2006)
The article deals with the high-accuracy global positioning system (GPS) survey equipment being used in Modesto, California. For Modesto, starting over meant hiring and training four computer aided design technicians in 2003 to perform computerized line work. The city created an accurate basemap using the same GPS equipment that captured its infrastructure which GIS Coordinator Robert Beckler used to improve GIS data sets.